SARS-CoV-2 Poorly Replicates in Cells of the Human Blood-Brain Barrier Without Associated Deleterious Effects - Constant, Orianne; Barthelemy, Jonathan; Bolloré, Karine; Tuaillon, Edouard; Gosselet, Fabien; Chable-Bessia, Christine; Merida, Peggy; Muriaux, Delphine; Van de Perre, Philippe; Salinas, Sara; Simonin, Yannick (Frontiers in Immunology, 2021)
Various neurological symptoms have been associated to infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) including headache, fever, anosmia, ageusia, but also, encephalitis, Guillain-Barre syndrome and ischemic stroke. Responsible for the current coronavirus disease (COVID-19) pandemic, SARS-CoV-2 may access and affect the central nervous system (CNS) by several pathways such as axonal retrograde transport or through interaction with blood-brain barrier (BBB) or blood-cerebrospinal fluid (CSF) barrier. Here, we explored the molecular and cellular effects of direct SARS-CoV-2 infection of human BBB cells. We observed low replication of SARS-CoV-2 that was accompanied by very moderate inflammatory response. Using a human in vitro BBB model, we also described weak replication levels without strong inflammatory response or modulation of endothelium integrity. Finally, using serum samples from COVID-19 patients, we highlighted strong concentrations of pro-inflammatory factors that did not perturb BBB integrity after short term exposure. Altogether, our results show that the main mechanism of brain access following SARS-CoV-2 infection does not seem to be directed by brain infection through endothelial cells.